МЕТОД ОЦІНКИ СТАНУ ІЗОЛЯЦІЇ ВІДКЛЮЧЕНИХ ПРИЄДНАНЬ МЕРЕЖІ 6-10 кВ З ІЗОЛЬОВАНОЮ НЕЙТРАЛЛЮ - Гребченко, М.В.; Кожухар, О.В.; Демченко, О.В. (Інститут електродинаміки НАН України, Київ, 2016)
The main provisions of the method that allows you to automatically assess the condition of electrical equipment disconnected connections and insulation. The method is based on the detection of asymmetry parameters of electrical equipment for which the charge is used tanks connection with DC voltage and the second examines the parameters of the transition process of the discharge, which occurs after switching off the DC voltage. The results of studies under the existing substation. References 3, figures 3.